2007
DOI: 10.1111/j.1439-0531.2007.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Endometrium in Endocrine Regulation of the Animal Oestrous Cycle

Abstract: A critical analysis of the results of research in the function of the endometrium was carried out and a view point presented. The role of the endometrium in endocrine regulation of the oestrus cycle can be summarized as follows: 1. The transfer of prostaglandin F(2alpha) (PGF(2alpha)) from the uterus to an ovary, which causes luteolysis, occurs mainly via the lymphatic pathways. 2. The system of retrograde transfer of PGs enables PGF(2alpha) and PGE(2) to reach the myometrium and endometrium with arterial bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 87 publications
0
26
0
2
Order By: Relevance
“…Consistent with earlier observations , Edqvist et al 1978, Bosu et al 1984, Meyer et al 1989, Kö nigsson et al 2001 maternal PGFM levels were still basal or only slightly elevated around the time of onset of prepartal luteolysis. However, this observation does not necessarily contravene a role of PGF 2a of cotyledonary origin as the luteolytic signal in prepartal cows, as maternal PGFM levels in peripheral blood might not closely reflect the local availability in the ovaries as has also been discussed for luteolysis in cyclic animals (Krzymowski & Stefań czyk-Krzymowska 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with earlier observations , Edqvist et al 1978, Bosu et al 1984, Meyer et al 1989, Kö nigsson et al 2001 maternal PGFM levels were still basal or only slightly elevated around the time of onset of prepartal luteolysis. However, this observation does not necessarily contravene a role of PGF 2a of cotyledonary origin as the luteolytic signal in prepartal cows, as maternal PGFM levels in peripheral blood might not closely reflect the local availability in the ovaries as has also been discussed for luteolysis in cyclic animals (Krzymowski & Stefań czyk-Krzymowska 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Aralla et al [18] demonstrated that elevated expression of AQP5 in the apical plasma membrane of uterine epithelial cells coincides with concentrations of progesterone (P 4 ) in plasma. The increased endometrial expression of AQP5 and AQP9 in the late luteal phase may be connected to structural changes in porcine endometrium which occur during this stage of the estrous cycle (for review see [44,45]).…”
Section: Discussionmentioning
confidence: 99%
“…A possible scenario has been proposed that a redirection of PG takes place, switching from an endocrine direction towards the uterine vasculature to a lumen-directed exocrine-driven synthesis (Bazer & Thatcher 1977), although there are convincing doubts favoring a retrograde transfer in the area of the mesometrium (Krzymowski & Stefanczyk-Krzymowska 2008). Major assumptions are that the epithelial endometrium can specifically transport PG in either apical or basal direction as well as the conceptusderived anti-luteolytic signal acts as a principal director (Ziecik et al 2006).…”
Section: Discussionmentioning
confidence: 99%